“White World, Not a Sound.” Paternal Spaces in Samuel Beckett’s Embers - Kisiel, Michał (Romanica Silesiana)
This paper aims at the interpretation of the father as an empty figure of authority in Samuel Beckett’s radio play entitled Embers. Through the close-reading of this play and the analysis of the relations between the protagonist and the two feminine characters, Ada and Addie, it demonstrates how the father figure coincides with the classical impasse of Beckett’s oeuvre: the subject unable to manifest itself. Due to that fact, the father is presented in the constant process of wearing his authorial space out. It is eventually demonstrated that in Embers the subject is coerced to balance between its self-deconstruction and the paternal violence: its focus on its own materiality results in the collapse of language, whereas overt attention on the linguistic cognition puts forward the logic of remnants resisting father’s orders, be it in the form of sound collage, or material element immune to symbolisation.